Mesoproterozoic surface oxygenation accompanied major sedimentary manganese deposition at 1.4 and 1.1 Ga. Issue 1 (27th September 2022) - Spinks, Sam C.; Sperling, Erik A.; Thorne, Robert L.; LaFountain, Felicity; White, Alistair J. R.; Armstrong, Joseph; Woltering, Martijn; Tyler, Ian M.
Abstract: Manganese (Mn) oxidation in marine environments requires oxygen (O2 ) or other reactive oxygen species in the water column, and widespread Mn oxide deposition in ancient sedimentary rocks has long been used as a proxy for oxidation. The oxygenation of Earth's atmosphere and oceans across the Archean‐Proterozoic boundary are associated with massive Mn deposits, whereas the interval from 1.8–1.0 Ga is generally believed to be a time of low atmospheric oxygen with an apparent hiatus in sedimentary Mn deposition. Here, we report geochemical and mineralogical analyses from 1.1 Ga manganiferous marine‐shelf siltstones from the Bangemall Supergroup, Western Australia, which underlie recently discovered economically significant manganese deposits. Layers bearing Mn carbonate microspheres, comparable with major global Mn deposits, reveal that intense periods of sedimentary Mn deposition occurred in the late Mesoproterozoic. Iron geochemical data suggest anoxic‐ferruginous seafloor conditions at the onset of Mn deposition, followed by oxic conditions in the water column as Mn deposition persisted and eventually ceased. These data imply there was spatially widespread surface oxygenation ~1.1 Ga with sufficiently oxic conditions in shelf environments to oxidize marine Mn(II). Comparable large stratiform Mn carbonate deposits also occur in ~1.4 Ga marine siltstones hosted in underlying sedimentary units. These deposits are greater or at least commensurate in scale (tonnage) to those that followed the major oxygenation transitions from the Neoproterozoic. Such a period of sedimentary manganogenesis is inconsistent with a model of persistently low O2 throughout the entirety of the Mesoproterozoic and provides robust evidence for dynamic redox changes in the mid to late Mesoproterozoic.